From Farmers to Cowboys: Rural American Identity and Community in Manawa, Wisconsin, 1848-1970 - Heideman, Heidi Ann (My University, 2014)
Farming and lumber production figuratively and literally shaped the landscape of Waupaca County, Wisconsin between 1848 and 1948. Ethnic identity further shaped these rural Waupaca County neighborhoods amongst others of the same or similar ethnic backgrounds. However, as the 1950s began, changes in technology and cultural identity began changing life in rural Waupaca County. Inventions like the combine lead to the end of community shared work like threshing, and neighborhoods no longer needed to work together to harvest crops or perform other essential duties on the farm. Rural schools began consolidating because of better bus transportation. Ethnic traditions that were community unifiers, such as German-language church services ended in this time period as younger generations discontinued ethnic language use. However, these practices fostered and anchored their communities. Manawa, Wisconsin and the surrounding rural townships of Little Wolf and Union, Wisconsin are a case study for how settlers built a community between 1848 and 1890, their children and grandchildren maintained it between 1890 and 1950, and their descendants redefined it beginning in the 1950s. In 1959, the people of Manawa inadvertently created a community unifying event when their chapter of the Lions Club decided to host a rodeo in the middle of Wisconsin in a community surrounded by farms, not ranches. Yet, rodeo resounded with people in and around Manawa because it appealed to their common rural identity, and became a new community-unifying tradition in Manawa.
Keywords: Country life--Wisconsin--Waupaca County; Farm life--Wisconsin--Waupaca County; Waupaca County (Wis.)--History; Waupaca County (Wis.)--Social life and customs; Manawa (Wis.)--History